The Concept and Legal Basis for the Transfer of Persons Sentenced to Deprivation of Liberty to Serve a Sentence in a Foreign State in the Field of International Cooperation of Post-Soviet Countries - Abdulloev, Parvyz S.; Serebrennikova, Anna V.; Minyazeva, Tatiana F.; Dobryakov, Denis A.; Trefylov, Aleksandr A. (International Journal of Criminology and Sociology, 2021)
The purpose of the study is to analyse the definition and legal basis of the concept of transfer of persons sentenced to imprisonment. The main research methods were theoretical: analysis and synthesis, classification. The article discusses topical issues related to the concept and legal grounds for the transfer of persons sentenced to imprisonment to serve their sentences in the framework of international cooperation. The article analyses the norms of international legal acts and national legislation of post-Soviet countries. It is noted that, among other types of transfer of persons, a special place is occupied by the transfer of a convicted person for the execution of a sentence, which testifies to the relevant practice of post-Soviet states. But the transfer of convicted persons to serve a sentence has a history of legal regulation for a little more than half a century, therefore, both in legal regulation and in the theory of criminal procedure there is no single approach to defining the concept of transfer of convicted persons. The author comes to the conclusion that the transfer of persons to a foreign state to serve their sentences is ensured by effective international cooperation in the field of criminal proceedings. The practical significance of the study lies in the fact that an idea is proposed for the development and improvement of national criminal legislation, as well as the effectiveness of actions aimed at resolving this issue.